Peningkatan Belajar Peserta Didik Pada Mata Pelajaran Matematika Kelas 5 Dengan Menggunakan Kotak Faktorisasi Prima - Suwardi, Suwardi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to increase students' activeness and understanding of learning material regarding Greatest Common Factor (FPB) and Least Common Multiple (KPK) using the prime factorization box method, as well as to improve student learning outcomes. The research was carried out in September and October at SDN 1 Glagah, Jatinom District. The research subjects consisted of 18 fifth grade students, with 14 male students and 4 female students. The use of prime factorization boxes as a guide in teaching and learning activities has proven to be effective in improving mathematics learning outcomes. The research instrument used was a formative test, which resulted in the finding that the application of this method was able to increase students' understanding and activeness, as well as achieve a significant increase in their learning outcomes. The results of this research provide a positive contribution to the development of more interesting and effective mathematics learning methods.